Electron Energy‐Loss Spectroscopy of Spatial Nonlocality and Quantum Tunneling Effects in the Bright and Dark Plasmon Modes of Gold Nanosphere Dimers. Issue 1 (7th June 2018) - Zhang, Qiang; Cai, Xiangbin; Yu, Xiang; Carregal‐Romero, Susana; Parak, Wolfgang J.; Sachan, Ritesh; Cai, Yuan; Wang, Ning; Zhu, Ye; Lei, Dang Yuan
Abstract: Herein, a theoretical and experimental electron energy‐loss spectroscopy (EELS) study on gold nanosphere dimers is presented, with interparticle distance d of the dimers varying from 10 nm to a few angstroms. Injecting an electron beam at the edge or the gap of the dimers excites their longitudinal bonding dipolar mode (BDM) or antibonding dipolar mode (ADM), respectively. Together with comprehensive EELS calculations within the frameworks of a classical local model, a hydrodynamic nonlocal model, and a quantum‐corrected model (QCM), it is revealed that spatial nonlocality and electron tunneling have distinctively different effects on the plasmonic properties of BDM and ADM, such as resonant energy and intensity variation. Specifically, the spatial nonlocality effect blue‐shifts the BDM energy and decreases its EELS intensity at d < 3 nm compared to the classical local results, while the electron tunneling effect induces a much weaker charge transfer mode (CTM) at d < 0.3 nm. However, both effects have little impact on the ADM energy though they indeed affect its EELS intensity in dramatically different manners. The experimental EELS spectra measured at varied gap size are qualitatively consistent with the numerical calculations. These results may contribute to further understanding of quantum mechanical effects in different kinds of hybridized plasmon modes in strongly coupled metallic nanostructures. Abstract : Spatial nonlocality and quantum tunneling effects in the bright and dark plasmon modes of single gold nanosphere homodimers are comparatively studied using electron energy‐loss spectroscopy and full‐wave numerical modeling. The results by Zhang et al. disclose that these quantum mechanical effects have distinctively different impact on the plasmonic properties of the two modes. In particular, the authors show that the electron tunneling is totally forbidden in the dark antibonding mode.